Defining end-of-life care from perspectives of nursing ethics - Izumi, Shigeko (Seiko) (Nursing ethics, 2012)
Despite increasing interests and urgent needs for quality end-of-life care, there is no exact definition of what is the interval referred to as end of life or what end-of-life care is. The purpose of this article is to report our examination of terms related to end-of-life care and define end-of-life care from nursing ethics perspectives. Current terms related to end-of-life care, such as terminal care, hospice care, and palliative care, are based on a medical model and are restrictive in terms of diagnosis and prognosis. Using codes of ethics for nurses as a framework, we attempt to identify people to whom nurses are responsible to provide end-of-life care and develop a definition of end-of-life care that is more inclusive and applicable to a broader range of people who would benefit from end-of-life care by nurses and other health-care providers.